Facile CH arylation using catalytically active terminal sulfurs of 2 dimensional molybdenum disulfide. Issue 44 (31st October 2018) - Hwang, Eunhee; Mi Lee, Sae; Bak, Sora; Min Hwang, Hee; Kim, Hyunjung; Lee, Hyoyoung
Graphical abstract: Highlights: Unprecedented MoS2 catalyzed for direct CH arylation. Catalytically active terminal sulfurs of MoS2 for CH arylation. High reusability and simple separation of heterogeneous catalyst. Abstract: The first methodology of CH arylation of heteroarene via 2D transition metal dichalcogenides that have catalytically active edge functional groups was described. The terminal sulfur groups could effectively catalyze a formation of an azo-linked intermediate with aryl diazonium salts, leading to produce heteroarenes with good yields. This novel methodology using bulk 2D transition metal dichalcogenides that have catalytically active edge functional groups can apply for various reactions to achieve CC bond formation in the fields of heterogeneous catalysis that is easily separable, highly reusable, and inexpensive method.